Aratati ca 2x +6 supra x (patrat) +4x+3=2 supra x+1
Răspunsuri la întrebare
Răspuns de
42
(2x + 6) / (x² + 4x + 3) = 2*(x + 3) / (x² + 3x + x + 3) = 2(x+3) /[x(x+3) + (x + 3)] =
= 2(x + 3) / (x + 3)(x+1) = se simplifica (x+3) cu (x+3) = 2 / (x + 1) cctd
= 2(x + 3) / (x + 3)(x+1) = se simplifica (x+3) cu (x+3) = 2 / (x + 1) cctd
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă